Pengembangan Bahan Ajar Laju Reaksi Dengan Multipel Representasi Berbasis Inkuiri - Pahriah, Pahriah; Hendrawani, Hendrawani (Hydrogen: Jurnal Kependidikan Kimia, 2018)
This development aims to determine the characteristics and feasibility of multipleinquiry-based representation modules in the reaction rate material through theADDIE stage (Analyze, Design, Development Implementation and Evaluation)developed by Thiagarajan. This research and development was carried out untilthe development stage with adjustments based on development needs. Theassessment instrument used to determine the feasibility of the module is aquestionnaire sheet. The module feasibility was assessed by 2 material experts, 1media expert, 1 linguist, 1 colleague, 1 practitioner, and 10 students as subjects.Students involved in this study came from chemistry education study programsthat had undergone basic chemistry courses through limited trials. The data onthe value of the grievances obtained are still in the form of qualitative data andthen processed into quantitative data. Quantitative data are analyzed for eachaspect of the assessment. The final score obtained is converted to the level ofproduct feasibility qualitatively with the guidelines according to the criteria ofthe assessment category. The results of expert validation showed the averagepercentage (a) of material experts was 84% with very feasible categories; (b)media experts 90% with very decent categories; (c) linguists 97% with verydecent categories; (d) colleagues 79.6 categories worth%; (e) practitioners86.4% are very decent categories. The average response of students to productdevelopment results 89.5% with a very feasible category. This shows that themodules developed are feasible to be used at the stage of large-scale trials.